Bricolage and Entrepreneurial Branding in Finnish Tourism Business SMEs - Suomi, Kati; Aro, Kaisa (Springer Nature, 2025)
The literature on entrepreneurial marketing has grown over the past 25 years, but entrepreneurial branding remains under-studied. The purpose of the present study was to conceptualize entrepreneurial branding in the context of tourism small- and medium-sized enterprises (SMEs). Firstly, this study seeks to add to the literature on entrepreneurial branding by developing a new definition of entrepreneurial branding, by looking at literatures on both ‘entrepreneurial’ and ‘branding’ addressing the limitations of existing definitions to offer a more complete conceptualization. Secondly, it explores whether and how tourism business SMEs employ bricolage in their entrepreneurial branding. The study adopts a qualitative approach with abductive reasoning. In total, 20 interviewees representing 16 Finnish tourism SMEs were interviewed. The findings demonstrate resource constraints faced by tourism SMEs in entrepreneurial branding. Unique features of the place, such as history and heritage of place, were significant sources for building a unique brand identity for the SMEs, often at little cost. The study exemplifies how companies use domains of bricolage (Baker and Nelson in Administrative Science Quarterly 50(3):329–366, 2005) to manage resource constraints. The study offers new insights into the contents of entrepreneurial bricolage domains (physical inputs, labor, skills, customers, and the institutional environment) within a specific context, while also suggesting a new bricolage domain in entrepreneurial branding—namely, media bricolage. This domain refers to companies’ innovative and proactive generation of unpaid or low-cost media coverage in different channels for the purposes of brand building.